PENGARUH MANAJEMEN MODAL KERJA, LEVERAGE DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERGABUNG DI BURSA EFEK INDONESIA 2022 - Alamsyah, Aninda Adelia Anugrah; Sarita, Buyung; Hamid, Wahyuniati; Budi, Nuryamin; Damau, Unika Oktaviani (Jurnal Manajemen dan Kewirausahaan, 2024)
This research aims: (1) to determine the effect of working capital, leverage and sales growth on profitability in manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2022. (2) to determine the effect of working capital on profitability in manufacturing companies listed on the Indonesian Stock Exchange (BEI) 2022. (3) Knowing leverage on Profitability in Manufacturing Companies Listed on the Indonesia Stock Exchange (BEI) 2022. (4) Knowing sales growth on Profitability in Manufacturing Companies Listed on the Indonesia Stock Exchange (BEI) 2022. The population in this research is real estate property and building construction companies. The analytical tool used in this research uses multiple linear regression. Research results: (1) Working capital management variable (X1) has a positive and significant effect. This means that improving working capital management can increase profitability. (2) The Leverage variable (X2) has a positive and insignificant effect on profitability, meaning that because of the high level of leverage there will be a high risk which is indicated by the presence of greater debt costs. (3) The sales growth variable (X3) has a negative and significant effect on profitability, meaning that sales in the current year have decreased compared to sales in the previous year, which can cause sales to decrease or be negative.